Powering Growth: The Dynamic Impact of Renewable Energy on GDP in ASEAN-5 - Rahman, Mahfuzur; Keat, Ngu Wang; Masud, Md Abdul Kaium; Albaity, Mohamed (International Journal of Energy Economics and Policy, 2024)
This study investigates the dynamic relationships between renewable energy consumption, labor force, gross fixed capital (GFC), and GDP across ASEAN-5 nations from 1984 to 2020. Utilizing data from the World Development Indicators (WDI), the Energy Information Agency (EIA), and national labor statistics, we employ unit root tests, ARDL bound testing for cointegration, and Toda-Yamamoto causality procedures. Our findings indicate significant long-term cointegration between the studied variables in Indonesia and the Philippines, suggesting persistent economic relationships, while results for Malaysia show no cointegration and remain inconclusive for Thailand. The economic analysis reveals that GFC robustly drives GDP growth across these countries, whereas the impacts from labor force and renewable energy consumption are more variable. Causality tests further demonstrate that renewable energy consumption significantly fosters GDP growth in Indonesia, Malaysia, and Singapore, aligning with the growth hypothesis. Conversely, findings for the Philippines and Thailand support the neutrality hypothesis, indicating no direct causal impacts. These insights underline the crucial role of tailored renewable energy strategies to enhance economic growth and sustainability in ASEAN-5, providing valuable policy implications for regional energy governance.